Controlling excludability in the evolution of cooperation - Dionisio, F. (2010)
Background: A tragedy of the commons arises if individuals cannot protect their future use of a depletable resource, and individual fitness increases if individuals exploit the resource at rates beyond sustainability. Natural selection then forces the individuals to diminish, perhaps even to destroy, their resource. One way to protect future use is privatization - that is, locally excluding rivals from the resource. Another is to reduce rivalry among individuals by restricting exploitation rates.